A 391‐Year Summer Temperature Reconstruction of the Tien Shan, Reveals Far‐Reaching Summer Temperature Signals Over the Midlatitude Eurasian Continent. Issue 22 (24th November 2019) - Chen, Feng; Yuan, Yujiang; Yu, Shulong; Chen, Fahu
Abstract: The Tien Shan is the largest independent latitudinal mountain ranges in Eurasia, but due to a lack of long‐term instrumental data, knowledge of past temperature variability in the Tien Shan is limited. In this paper, a maximum latewood density (MXD) chronology of Schrenk spruce ( Picea schrenkiana ) was constructed from the Tien Shan, Central Asia. Correlation analyses indicate that the MXD variations of spruce trees in the Tien Shan are mainly limited by summer temperature variations. The July–August mean temperature was reconstructed for the Tien Shan back to 1615 CE. The temperature reconstruction explained 42.9% of the instrumental variance (1930–2005). This reconstruction successfully captured the past temperature variabilities in the Tien Shan and enabled visualization of the cool climate before 1850s and the climatic warming after the 1850s. Agreement among the temperature series of the Tien Shan and regional temperature records based on MXDs from Eurasia suggested that our reconstruction had good reliability, captured some warm/cold periods, and first principal component of these MXD records showed that there are strong large‐scale temperature forcings in Eurasia. Our study also showed that there is a linkage between temperature changes in Central Asia and the atmospheric circulations of the middle‐high latitude westerly region and the sea surface temperatures of both the Pacific Ocean and the Atlantic Ocean. The positive correlations among the principal component time series of regional temperature reconstructions based on MXDs and Northern Hemisphere temperature reconstructions revealed that the MXD chronologies from Central Asia have the potential for developing large‐scale temperature reconstruction. Key Points: Tree rings provide a summer temperature record of the Tien Shan since 1656 CE There was reasonable agreement between our temperature reconstruction and cold and warm periods previously estimated using MXDs from Eurasia Tree ring record shows some close relationships with climate forcings, included volcanic eruptions and summer North Atlantic Oscillation